Kinematic analysis of rotary car parking system mechanism - Nursalim, Iim; Saputra, Hendri Maja; Ismail, Nanang; Gunawan, Teddy Surya (Institute of Electrical and Electronics Engineers Inc., 2018)
Due to the increased number of vehicles in big cities, parking space become an inherent problem. Recent research on rotary car parking system (RCPS) showed its potential in saving space and time during parking. This paper discussed the kinematic analysis of the RCPS based on the given angle providing automatic power measurement while reducing calculation errors in the final design. The proposed RCPS is designed using six slots, in which each slot has the capability to accommodate only one car. The trigonometric approach is used to derived the equations, in which the RCPS mechanism achieved using different angle, including 0° - 90°, 90° - 166°, 166° - 180°, 180° - 194°, 194° - 270° and 270° - 360°. In this paper, two equations were derived to determine the optimum coordinate positions and the minimum power required. Simulation results showed that when all six slots were occupied, the total mechanical load is 1800 kg. The maximum power requirement is 492.73 watt for the unbalanced load.